Tracing The Practice and The Impact of Divorce: Exploring Issues From Ponorogo District (Program Studi Hukum Keluarga Islam, 2025)
The large number of divorce cases that occur in Indonesia is a problem that must be resolved and addressed as soon as possible, so that the issue of divorce does not continue to occur because it has various negative impacts, especially for children and families. Although there are many studies on divorce in Indonesia in general, there are still few studies that specifically examine the causes and impacts of divorce in the Ponorogo Regency area. This study aims to analyze the causes as well as the impact of divorce practices that occur in the Ponorogo Regency Religious Court. The type of research used is descriptive qualitative with data collection techniques of observation, interview, and documentation. The data analysis technique uses data collection, data condensation, data presentation, and conclusion drawing. In data validity, researchers use source triangulation. The results showed that family divorces that occurred in Ponorogo Regency were caused by various things; first, the economy, the husband's lack of income and the wife's inability to manage family finances. Second, infidelity. Third, arranged marriages due to the absence of love from one of the parties, and fourth, polygamy carried out under the wrong conditions. Family divorce has positive and negative impacts on various parties such as the perpetrator, children, family environment and society.